Russia as "Pattern or Example": John Milton's A Brief History of Moscovia (1682). Issue 2 (4th May 2021) - Binney, Matthew W.
ABSTRACT: Scholars agree that Milton offers primarily a negative view of Russia in A Brief History of Moscovia, yet some have also identified positive descriptions of Russian czars, people, and church. Negative and positive descriptions work together in relation to Milton's view of the past and his focus on one state, offering a "Pattern or Example" that emerges from his distinctive political philosophy and represents his ethical concerns. Milton demonstrates that sovereigns and subjects must exercise their reason and liberty of choice to choose the common good over private interest; the church must reject superstition and formality to liberate the mind; and a Protestant tradition cultivates independence. These are realized by Aristotelian kings, a vigilant regenerate, and liberty of choice in liturgy and conscience. These ethical concerns offer at once a reproach to leaders and events and also ideas and rhetoric for framing late seventeenth-century political discourse that represents Russia.